Verification of the Cage Stability and the Superiority of Titanium Coating in the Bone Fusion of Transforaminal Lumbar Interbody Fusion Using Polyetheretherketone (PEEK) Cages - Muhammad Saqib, Tauseef Raza, Sajjad Mehmood, Usman Akmal, Muhammad Asad Iqbal, Saeed Taj Din, Mian Iftikhar Ul Haq (Pakistan Journal of Medical & Health Sciences, 2023)
Background: PEEK spinal cages are now commonplace in transforaminal lumbar interbody fusion, credited with excellent strength and stiffness. Paradoxically, their bioinert character hampers intimate bone ingrowth around the implant. To address this shortcoming, researchers have experimented with surface treatments, most notably titanium plasma-spray coating, that promise tighter surface-to-bone contact and improved fixation. The present investigation compares clinical and radiographic outcomes between titanium-coated and standard PEEK cages in a homogenous cohort of patients after TLIF. Methods: Between January 2022 and January 2023, a prospective comparative study evaluated ‘71 patients who underwent transforaminal lumbar interbody fusion for degenerative lumbar spine disorders’. The cohort was evenly split: Group A received titanium-coated poly-ether-ether-ketone cages (n=35) and Group B received standard uncoated cages (n=36). Clinical results were measured with the Visual Analog Scale for pain and the Oswestry Disability Index for functional capability. Imaging outcomes were evaluated for fusion quality, cage subsidence, and the restoration of disc height and segmental lordosis. Statistical analysis was performed with SPSS, and a p-value of less than 0.05 was deemed significant. Results: Fusion was achieved in 85.7% of patients in the titanium-coated group, compared to 61.1% in the uncoated group (p=0.018). Time to fusion was shorter in the coated group (7.2 ± 1.1 months vs. 8.6 ± 1.5 months; p=0.001). Disc height and segmental lordosis restoration were also superior in the titanium group. VAS and ODI scores showed significantly greater improvement at 12 months. Complication and reoperation rates were lower in the titanium-coated group but not statistically significant. Conclusion: Titanium-coated PEEK spinal cages appear to promote stronger bone fusion and better functional results after transforaminal lumbar interbody fusion, yet they do not add new safety risks. Such evidence bolsters the increasing use of surface-modified devices in lumbar fusion surgery. Keywords: Transforaminal lumbar interbody fusion, PEEK cage, titanium coating, spinal fusion, cage stability, bone integration